Cultivating Intercultural Attitudes among EIL learners: A Case Study of Undergraduates - Muhammad Waqar Ali; Muhammad Iqbal; Sareer Badshah (University of Chitral Journal of Linguistics and Literature, 2023)
Teaching of English as an international language (EIL) necessitates promoting intercultural communicative competence (ICC) to enable the individual to survive and progress in multicultural societies. It thereby requires them to develop intercultural attitudes—one of the essential components of ICC. The current paper strives to fathom their intercultural  attitudes before and after the intervention, and to measure the impact of the treatment on their intercultural attitudes. Based on the material designed for promoting intercultural competence, a semester-long course was carried out as the intervention. Unlike the control group, the treatment group was exposed to the treatment. A self-report survey was administered to both groups before and after the treatment. Though both groups reported improvement in their attitudes, the mean differences and effect size values for the cumulative scale and subscales indicate a substantial difference between the attitudes of the two groups; it thereby may be inferred that the treatment proved to be effective in cultivating intercultural attitudes. Furthermore, female participants slightly surpassed the male participants in certain attitudes, but the difference infinitesimal.